2013
DOI: 10.5935/0103-5053.20130152
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Synthesis of SAPO-11 for the Methylation of Naphthalene with Methanol by Varying Templates and Template Content

Abstract: DEA > DIPA and the most suitable DPA content was nDPA/Al2O3 = 1.2. N2 adsorption-desorption results showed that SAPO-11(DPA,1.2) exhibited the broadest pore size distribution, the highest BET specific surface area and the largest pore volume among all the SAPO-11 samples. SAPO-11(DPA,1.2) exhibited high catalytic performances in the methylation of naphthalene due to its high crystallinity, high external surface and broad pore size distribution. The pore structure of SAPO-11 zeolite, rather than its acidity, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The ratio of 2,6-/2,7-DMN is an essential parameter of alkylation . The ratios of 2,6-/2,7-DMN at varied WHSVs and temperatures appear in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of 2,6-/2,7-DMN is an essential parameter of alkylation . The ratios of 2,6-/2,7-DMN at varied WHSVs and temperatures appear in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of 2,6-/2,7-DMN is an essential parameter of alkylation. 62 The ratios of 2,6-/2,7-DMN at varied WHSVs and temperatures appear in Figure 9. It was shown that the ratio was higher when the amount of Al doping was less.…”
Section: Catalytic Activity Evaluationmentioning
confidence: 99%
“…The catalytic efficiency of SAPO-11 in the stated processes is influenced by the strength and concentration of acid sites, crystal size, and characteristics of the porous structure. At present, some success has been achieved in the development of ways to regulate the concentration and localization of acid sites [ 18 , 19 , 20 , 21 , 22 , 23 ], as well as the crystal size and characteristics of the secondary porous structure [ 24 , 25 , 26 , 27 , 28 , 29 ]. At the same time, despite the advancements in synthesizing SAPO-11 silicoaluminophosphate, the crystallization mechanism remains insufficiently studied, knowledge of which will allow us to move to the directed control of the above-mentioned characteristics of these molecular sieves and the creation of more efficient catalysts based on them [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, methylation of 2-methylnaphthalene (2-MN) or naphthalene (NA) with methanol over zeolite catalyst is regarded as a desirable process for the synthesis of 2,6-DMN. Various kinds of medium- or large-pore zeolites, such as HZSM-5, HSAPO-11, HZSM-11, HZSM-12, HBeta, HY, HMOR, HMCM-22 etc., ,− have been investigated. Generally, the large-porous zeolites show relatively high activity but low 2,6-DMN selectivity and 2,6/2,7-DMN ratio. ,,,, On the contrary, medium-porous zeolites (especially HZSM-5 or HSAPO-11) exhibit the high selectivity of 2,6-DMN and β,β-DMN but the relatively low conversion of 2-MN. , , These are directly related to the differences in the molecular diffusion and the porous shape selectivity between large and medium pore. …”
Section: Introductionmentioning
confidence: 99%